Upaya Meningkatkan Keterampilan Tolak Peluru Melalui Modifikasi Alat untuk Siswa Menegah Pertama - Marsianus; Maksum, Henry (Universitas PGRI Pontianak, 2023)
The purpose of this study is to determine the improvement of shot put skills among 8th grade students at SMP Negeri 1 Tebas, Sambas Regency, through the use of modified equipment in physical education. This research employs the action research method following the Kemmis and McTaggart model, which includes four stages: planning, implementation, observation, and reflection. The instruments used in this study are shot put skill tests and observations. The results show that modifying the equipment can enhance students' shot put skills. In the first cycle of action, 20 students (56%) passed the Minimum Competency Criteria (KKM) for the shot put skill test, compared to only 8 students (24%) in the pre-cycle. Furthermore, in the second cycle, 29 students (85%) passed the test. Therefore, modifying the equipment can significantly improve students' shot put skills.